Teaching through Flipping Classrooms a new innovation at Higher Education in Indonesia - Sappaile, Baso Intang; Siminto, Siminto; Sefrizal, Levy; Tarigan, Jenheri Rejeki; Roswati, Roswati; Sabur, Fatmawati (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Education in Indonesian tertiary institutions has recently been negotiating with him that there is a problem that arises in learning in the form of less effective classroom learning, because the time between teaching materials is not balanced and in delivering material it is too monotonous and boring because the The material being taught is in the form of lectures so that with this students will feel sleepy and not enthusiastic in learning. Therefore, learning with conventional methods such as listening to lectures in class tends to make students passive and ultimately makes teaching and learning activities unpleasant and boring. So the effort that must be made for this problem is how to overcome it. One of the newest innovative learning models based on learning videos and is believed to be a solution to this problem is teaching through a flipped classroom for new innovations in universities in Indonesia. This lesson guides students to study independently, with the help of videos they can study before going to class, so that by coming to class they will only do class activities that focus more on discussion activities and asking questions. Therefore this study aims to create students who are more active in discussing in class so that the discussion only discusses material that has been studied at home. So as to create a class atmosphere that is not quiet and creates active and enthusiastic students in learning. The existence of a learning model in the form of a Flipped Classroom will make it easier for lecturers and students in class activities, and this Flipped Classroom can be applied in Universities in Indonesia. The method used in this research is a quantitative method. The data obtained in this study is through the distribution of questionnaires containing statements. The questionnaire was created via Google Form. The results of this study explain that teaching through Flipped Classroom provides positive benefits in learning, becomes a solution in solving problems, and encourages student enthusiasm and will create local activity so that collaboration between individuals is created, and motivates the birth of new ideas. The conclusion of this study explains that teaching through Flipped Classroom can change a person to think more creatively, increase the ability and skills to create new things that are more creative, create an interesting learning environment, and build good communication between individuals. The limitations of this study are that researchers only conduct research at the tertiary level which basically can think more critically to deal with new things.